(untitled) (Global Journal of Science Frontier Research, 2019)
The application of magnetic nanoparticles (MNPs) in environmental and chemical engineering is progressively increasing, leading to the development of new surface modifications using green methodologies. Magnetite nanoparticles functionalized with Glutathione (Glutathione@MNPs) were synthesized by a novel eco-friendly method using glutathione as a reductant and stabilizer agent.Mercury adsorption was investigated at different initial pH values, contact time, temperatures and adsorbate-adsorbent concentrations. Maximum Hg2+ removal took place at pH 7.5. Adsorption dynamic data were best described by pseudo-second order rate equation, and adsorption equilibrium data were best fitted to Langmuir equation.Maximum adsorption capacities of 34.48 mg/g at 1 mg/L of initial conditions and 25°C was obtained. Regeneration of Glutathione@MNPs and recovery of Hg2+ was demonstrated using 0.1 M KI and HCl up to ten cycles of adsorption.